SUPPORT SYSTEM FOR MANAGEMENT DECISION-MAKING BY HEADS OF HYDROLOGICAL EMERGENCY SITUATIONS LIQUIDATION USING GEO-INFORMATION TECHNOLOGIES - Нavrys, A.; Veselivsky, R.; Pekarska, O.; Liubovetskyi, O.; Filippova, V. (Municipal economy of cities. Series: «Economy science», 2025)
The main purpose of the article is to create a management decision-making support system for the head of emergency liquidation of hydrological origin, which includes the use of geoinformation technology tools, in particular the ArcGIS software complex.